Adaptation and Psychometric Properties of the Posttraumatic Maladaptive Beliefs Scale (PMBS): Indonesian Version - Urip Purwono; Hanna Euodia Anggoh (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Posttraumatic Maladaptive Beliefs Scale (PMBS) was developed to measure maladaptive beliefs about current life circumstances that may occur following trauma exposure. This scale assesses maladaptive beliefs within three domains: (a) Threat of Harm,(b) Self-Worth and Judgment, and (c) Reliability and Trustworthiness of Others. Items for the PMBS were drawn from a larger preexisting measure that assesses a wide range of personal beliefs and reactions associated with trauma exposure. The construct validity of the PMBS was assessed to 155 adults trauma survivor in Indonesia. This article provides data to support the reliability and validity of the PMBS which has been adapted to Indonesian language. The results of Confirmatory Factor Analysis (CFA) showed that 13 out of 15 PMBS items showed a good goodness of fit model (CFI = 0.956; GFI = 0.927; SRMR = 0.071; TLI = 0.935). It can be concluded that PMBS has good psychometric properties so that it can be used in research and assessment.